1996
DOI: 10.1590/s0004-282x1996000200002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations of peripheral nervous system involvement in human chronic chagas disease

Abstract: -We conducted a clinical and electromyographical study in patients with Chagas' disease in the indeterminate or chronic stages of the illness. Altogether 841 patients were examined. Only 511 were admitted within the protocol; the remainder patients were rejected because they showed other causes able to damage the nervous system. Fifty two (10.17%) out of the 511 patients showed signs and symptoms of peripheral nervous system involvement in the form of sensory impairment and diminished tendon jerks suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Peripheral neuropathy has also been documented for Chagas' disease. Although mostly subclinical, some patients may present with mild sensory-motor findings (36,37). Our study suggests a revisiting of muscle and nerve pathology in patients with Chagas' disease for evidence of vasculitis.…”
Section: Discussionmentioning
confidence: 68%
“…Peripheral neuropathy has also been documented for Chagas' disease. Although mostly subclinical, some patients may present with mild sensory-motor findings (36,37). Our study suggests a revisiting of muscle and nerve pathology in patients with Chagas' disease for evidence of vasculitis.…”
Section: Discussionmentioning
confidence: 68%
“…The chronic infection is associated with degeneration of the ganglia of the autonomic nervous system, leading to megacolon, megaesophagus, and cardiac abnormalities, all of which can develop 10 to 30 years after initial infection. 74 Additionally, sensory peripheral neuropathy may be associated with the disease, as demonstrated by a study of patients with trypanosomiasis by Genovese et al 75 The mechanism by which Chagas disease causes autonomic nervous system pathology is debated, although some studies have suggested binding of autoantibodies to the nicotinic acetylcholine receptor and others have suggested a direct effect of the parasitemia. 74,76 Diagnosis of chronic Chagas disease is based on detection of IgG antibodies to T cruzi antigens.…”
Section: Parasites With Clinical Implications In the Pnsmentioning
confidence: 99%
“…Its deleterious effects in humans have been known for more than 100 years, usually thought to involve gastrointestinal and cardiac systems due to autonomic dysfunction [1,2]. However, some investigations have demonstrated not only autonomic nervous system abnormalities but also peripheral and central nervous system involvement [3]. In the latter case, cerebrovascular disease (CVD) is a recognized cardioembolic complication in patients with Chagas' disease [4] supported by clinical, epidemiological and pathological investigations [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%